Type I collagen from sea cucumber (Stichopus japonicus) and the role of matrix metalloproteinase-2 in autolysis. (June 2021) - Yan, Long-Jie; Sun, Le-Chang; Cao, Kai-Yuan; Chen, Yu-Lei; Zhang, Ling-Jing; Liu, Guang-Ming; Jin, Tengchuan; Cao, Min-Jie
Abstract: Autolysis is a major issue affecting the quality of sea cucumber during transportation and processing. To further clarify the mechanism, characteristics of type I collagen from sea cucumber Stichopus japonicas and its degradation by recombinant matrix metalloproteinase-2 (rMMP-2) were investigated. Scanning electron microscopic (SEM) images showed that the body wall of fresh sea cucumber with intact collagen fibrils was disaggregated after autolysis. Pepsin-soluble collagen of Stichopus japonicas ( Sj PSC) was prepared and its filamentous feature was observed using SEM. Circular dichroism spectrum analysis showed that Sj PSC had native triple helix structure and its denaturation temperature was 34.0 °C using differential scanning calorimeter. The α chain gene of Sj PSC encoding 1400 amino acid residues was cloned. A polyclonal antibody against Sj PSC was prepared and was used to detect collagen degradation during autolysis. The effect of rMMP-2 on the body wall strongly suggested that MMP-2 had an important role in sea cucumber autolysis by disaggregating collagen fibres into fibrils. Graphical abstract: Image 1 Highlights: Sj PSC was purified and its morphological features in the solution state were observed. A highly specific polyclonal antibody against Sj PSC was prepared. The α chain gene of Sj PSC was cloned. MMP-2 has an important role in the degradation of collagen fibrils during autolysis.